Effect of compost and urea nitrogen on growth and yield of sweet pepper (Capsicum annuum L.) and on some properties of the Gezira soil - Mahgoub, Manal M.; Abdelmalik, Altayeb M.; Babiker, Hashim M.; Mohamed, Ahmed Eltayeb A. (Gezira Journal of Agricultural Science, 2017)
Compost is stable humus like product resulting from biological decomposition of organic matter under controlled conditions. The objective of this study was to investigate the combined effect of compost with urea nitrogen on some soil properties, growth and yield of sweet pepper. This study comprised a number of experimentations conducted over two consecutive seasons (2009/10-2010/11) at the Experimental Farm of the Faculty of Agricultural Sciences, University of Gezira and laboratories of CIRAD in France. Compost was applied at 0, 10 and 20 t ha -1 combined with N at 0, 43 and 86 kg ha -1 in the form of urea. The results showed that application of compost alone or in combination with urea nitrogen improved soil properties and hence growth and yield of sweet pepper. Improvement of those parameters was more pronounced when the urea and compost were combined, especially at the higher rates. Combination of urea and compost presumably improved availability of nitrogen from the organic source to sweet pepper and, therefore, positively affected growth and yield of the crop. The extent of improvement was less when urea nitrogen and organic manures were applied in the same season. Hence, it could be recommended to fertilize sweet pepper with compost and urea at the rate of 86 kg N/ ha.